(untitled) (Journal of Rangpur Medical College, 2024)
Background: Proton pump inhibitors (PPIs) are widely prescribed medications used to treat conditions related to excessive stomach acid, such as gastroesophageal reflux disease (GERD), peptic ulcers, and Zollinger-Ellison syndrome. Despite their efficacy in managing acid-related disorders, the appropriate use of PPIs, particularly concerning the correct dosage remains a critical issue in clinical practice. Objective: This study aimed to assess the effectiveness of PPI therapy by ensuring appropriate dosage of PPI in patients with different comorbidities in medicine, surgery, and gastroenterology wards in Dhaka Medical College Hospital. Methods: This cross-sectional observational study was conducted at the Department of Pharmacology and Therapeutics, Dhaka Medical College, Dhaka, from July 2019 to June 2020. A total of 600 patients were selected as study subjects by purposive sampling technique. Data were collected and evaluated considering USFDA-approved indications, and the systematic review by Scarpignato et al. recommendations. Data were analyzed using descriptive statistics. Analysis of data was carried out by using Statistical Package for Social Science (SPSS) 22.0 for Windows. Results: Among 255 patients, who were prescribed PPIs for an appropriate indication, 129 (50.6%) patients were given PPIs in an appropriate dose, whereas the dose was inappropriate in 126 (49.4%) patients. The appropriate dose was followed mostly in the gastroenterology department (83.1%), followed by the medicine department (47.3%). Whereas in the surgery department, only 35% of patients were given PPIs with an appropriate dose and the difference in the usage of appropriate doses of PPIs among the three departments is significant with p-value <0.001. The most common comorbid condition was diabetes (110; 18.3%), followed by hypertension (91; 15.2%) and stroke (24; 4.0%). Conclusion: This study estimates that only 50.6% of the 255 patients received the appropriate PPI dosage. The gastroenterology department had the highest adherence to appropriate dosing (83.1%). Diabetes was the most common comorbidity among patients (18.3%), followed by hypertension (15.2%) and stroke. These results highlight the need for improved adherence to PPI dosing guidelines across departments to enhance therapy effectiveness. J Rang Med Col. September 2024; Vol. 9, No. 2: 44-49